2021
DOI: 10.1021/acsami.1c18190
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Foreign Body Response and Improved Antimicrobial Efficacy via Silicone-Oil-Infused Nitric-Oxide-Releasing Medical-Grade Cannulas

Abstract: Foreign body response and infection are two universal complications that occur with indwelling medical devices. In response, researchers have developed different antimicrobial and antifouling surface strategies to minimize bacterial colonization and fibrous encapsulation. In this study, the nitric oxide (NO) donor S-nitroso-N-acetylpenicillamine (SNAP) and silicone oil were impregnated into silicone rubber cannulas (SR-SNAP-Si) using a solvent swelling method to improve the antimicrobial properties and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 53 publications
(145 reference statements)
0
26
0
Order By: Relevance
“…Moreover, the fabricated NO-releasing non-fouling surface was also found to be non-cytotoxic toward mammalian fibroblast cells. A similar methodology was reported with other SR-based medical devices for the use of urinary catheters and insulin cannula with long-term NO release and reduced SNAP leaching and protein fouling in addition to excellent antibacterial, antifouling, and biocompatible properties. ,, This is a simple and promising approach to generate a LINORel surfaces on prefabricated medical devices and therefore holds huge potential in clinical translation. Recently, a novel method to generate NO-releasing Si oil with proactive antibacterial properties was reported that involved covalent immobilization of the NO donor to Si oil or generation of NO-releasing Si oil by nitrosation of thiolated Si oils. , Such oils can be infused on the PDMS surfaces that are often used for biomedical device applications to create antibacterial interfaces.…”
Section: Advancements In Nitric Oxide-releasing Multifunctional Biome...mentioning
confidence: 86%
See 3 more Smart Citations
“…Moreover, the fabricated NO-releasing non-fouling surface was also found to be non-cytotoxic toward mammalian fibroblast cells. A similar methodology was reported with other SR-based medical devices for the use of urinary catheters and insulin cannula with long-term NO release and reduced SNAP leaching and protein fouling in addition to excellent antibacterial, antifouling, and biocompatible properties. ,, This is a simple and promising approach to generate a LINORel surfaces on prefabricated medical devices and therefore holds huge potential in clinical translation. Recently, a novel method to generate NO-releasing Si oil with proactive antibacterial properties was reported that involved covalent immobilization of the NO donor to Si oil or generation of NO-releasing Si oil by nitrosation of thiolated Si oils. , Such oils can be infused on the PDMS surfaces that are often used for biomedical device applications to create antibacterial interfaces.…”
Section: Advancements In Nitric Oxide-releasing Multifunctional Biome...mentioning
confidence: 86%
“…(c) SR-SNAP-Si cannulas radically decreased the thickness of the fibrous encapsulation surrounding the implant in the mouse model after 21 days by 60.9 ± 6.1% relative to unmodified cannulas. Reproduced from ref . Copyright 2021 American Chemical Society.…”
Section: Advancements In Nitric Oxide-releasing Multifunctional Biome...mentioning
confidence: 99%
See 2 more Smart Citations
“…The instantaneous surface flux of NO from the fabricated incubation vials was assessed before blood exposure following our previously reported methods for blood-contacting materials (see Supporting Methods). 30,31 Total SNAP loading into the PET blood incubation vials was determined by first deswelling circular samples of the SNAP-swollen vials (∼1.03 cm 2 ) in 40% v/v benzyl alcohol in chloroform (1 mL) for 24 h. This process removes SNAP from the polymer and allows detection based on its absorption maximum wavelength (λ max = 340 nm). Using a standard curve, the total mass of SNAP (mg) removed from PET samples after deswelling in solution for 24 h was determined and normalized to the total weight of the sample prior to SNAP removal (mg of SNAP/mg of vial × 100%).…”
Section: Fabrication Of No and No+heparin Blood Incubationmentioning
confidence: 99%